2018
DOI: 10.1186/s12974-018-1333-z
|View full text |Cite
|
Sign up to set email alerts
|

Complement-dependent bystander injury to neurons in AQP4-IgG seropositive neuromyelitis optica

Abstract: BackgroundAquaporin-4-immunoglobulin G (AQP4-IgG) seropositive neuromyelitis optica spectrum disorder (herein called NMO) is an autoimmune disease of the central nervous system in which AQP4-IgG binding to AQP4 on astrocytes results in complement-dependent astrocyte injury and secondary inflammation, demyelination, and neuron loss. We previously reported evidence for a complement bystander mechanism for early oligodendrocyte injury in NMO. Herein, we tested the hypothesis that complement bystander injury, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 41 publications
(40 reference statements)
1
45
0
2
Order By: Relevance
“…Complement proteases interact with receptors C3Ra and C5aR, so-termed anaphylatoxin receptors, to form a membrane attack complex that targets cells and causes cell lysis. The same complement attack complex C5b9 is implicated in neuronal damage [183]. The membrane attack complex leads to inflammatory cell chemotaxis, opsonization and cell lysis.…”
Section: Viral Complement Control Proteinsmentioning
confidence: 99%
“…Complement proteases interact with receptors C3Ra and C5aR, so-termed anaphylatoxin receptors, to form a membrane attack complex that targets cells and causes cell lysis. The same complement attack complex C5b9 is implicated in neuronal damage [183]. The membrane attack complex leads to inflammatory cell chemotaxis, opsonization and cell lysis.…”
Section: Viral Complement Control Proteinsmentioning
confidence: 99%
“…A recent study provided evidence that in rat brain and astrocyte‐neuron cocultures, AQP4‐IgG and complement kill neurons through a complement bystander mechanism instead of injuring neurons directly. This proposed mechanism involves the diffusion of activated soluble complement components from complement‐injured astrocytes to nearby cells, leading to early neuronal injury near astrocytes even before gross plasma membrane permeabilization and uptake of the dead cells are observed . Using whole‐genome sequencing and genome‐wide SNP array, a recent genetic study identified three HLA alleles that are highly correlated with AQP4‐IgG‐seropositive patients .…”
Section: Complement‐dependent Cytotoxicitymentioning
confidence: 99%
“…The complement system plays a pivotal role in the innate immunity of CNS in aging and disease progression (16,23,48). The complement pathway is an important regulatory factor of innate immunity.…”
Section: Introductionmentioning
confidence: 99%